Exploring the Experiences of STEM Students in Writing Research: Insights, Challenges, and Strategies - Galdonez, Dominic Patric (Journal of Basic Education Research, 2025)
Purpose of the study: This study aims to explore and examine the experiences and narratives of thirty-two (32) students from the Philippine Science High School - Ilocos Region Campus (PSHS-IRC) as they engaged in conducting and writing STEM research. Methodology: The study used a descriptive phenomenological design to explore the research experiences of 32 students from PSHS-IRC. Data was collected via open-ended questionnaires and in-depth interviews. Thematic analysis identified key themes, validated through member checking and intercoder agreement, ensuring reliability and accuracy of insights. Main Findings: Research writing presents numerous challenges for students, including literature searching, resource limitations, procrastination, motivation, and time management. Key difficulties involve finding credible sources, organizing research, defining problems, and drafting sections like the methodology and conclusion. Strategies such as seeking help, improving sourcing techniques, and prioritizing tasks can mitigate these challenges, enhancing students’ research experience. Novelty/Originality of this study: This study highlights student challenges in research writing, providing insights for educators and administrators to improve research education. The findings also serve as a valuable reference for future studies in STEM education, offering guidance for scholars interested in exploring similar topics and enhancing academic support systems.